2010
DOI: 10.1590/s0104-14282010005000033
|View full text |Cite
|
Sign up to set email alerts
|

Influência da temperatura e da natureza do catalisador na polimerização do glicerol

Abstract: Resumo: Neste trabalho, a polimerização do glicerol na presença de catalisador ácido (H 2 SO 4 ou H 3 PO 4 ) e básico (NaOH), para produzir resinas termofixas foi investigada. Os resultados mostraram que as variáveis como a temperatura de reação, o tipo e a concentração do catalisador são críticas para a obtenção de bons rendimentos e seletividade para materiais poliméricos. Em condições otimizadas, i.e. H 2 SO 4 como catalisador, 140 °C por 24 horas, foi possível obter polímeros com 98% de seletividade. Após … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
2
10
0
2
Order By: Relevance
“…The FTIR spectrum from glycerol shows the transmission bands: 849 cm −1 C‐C stretching; 1030 cm −1 C‐O stretching; 1416 cm −1 , 908 cm −1 CH 2 ; 1108 cm −1 C‐OH; 2880 and 2932 cm −1 C‐H stretching and 3286 cm −1 O‐H stretching. These transmission bands are in agreement with the results obtained by Bilanovic et al and Medeiros . FTIR spectra from NRL and NRL‐glycerol showed that there is no covalent interaction between glycerol and NRL (not show additional transmission bands).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The FTIR spectrum from glycerol shows the transmission bands: 849 cm −1 C‐C stretching; 1030 cm −1 C‐O stretching; 1416 cm −1 , 908 cm −1 CH 2 ; 1108 cm −1 C‐OH; 2880 and 2932 cm −1 C‐H stretching and 3286 cm −1 O‐H stretching. These transmission bands are in agreement with the results obtained by Bilanovic et al and Medeiros . FTIR spectra from NRL and NRL‐glycerol showed that there is no covalent interaction between glycerol and NRL (not show additional transmission bands).…”
Section: Resultssupporting
confidence: 92%
“…Under these conditions, NRL and NRL‐glycerol membranes showed no hemolytic effects indicating no detectable disturbance of the red blood cell membranes. These results are similar to those obtained by Borges et al 8‐33 and Barros et al . The test was realized according to the international standard ISO 10993‐4:2002, showing that the membrane NRL‐glycerol has no cytolytic activity.…”
Section: Resultssupporting
confidence: 91%
“…Several studies have shown that glycerol can be condensed in the presence of acid catalysts to produce ether-type oligomers containing two to five units; [2][3][4][5][6][7][8][9] further reaction leads to the polymerization of glycerol, producing a thermosetting resin. 3,4 Moreover, via glycerol polymerization followed by pyrolysis on the surface of clay vermiculite, a carbon-coated composite with a surface area of 835 m 2 g −1 (essentially microporous, with a significant portion of mesopores) is obtained, and is used for dye adsorption. 10 Polymerization of glycerol produces a thermosetting polymer, which can be pyrolyzed, maintaining its structure.…”
Section: Introductionmentioning
confidence: 99%
“…The glycerol polymers produced can have different applications, as polyols substitutes, polivinylic alcohol, lubricant, row materials to produce resins and polyurethanes. 12 Glycerol can be a plasticizer agent when added to phenolic composite and can increase the elasticity and toughness of the phenolic materials. The presence of glycerol in the phenolic network reduces the characteristic brittleness of phenolic resins by decreasing to cross-link density of the cure composites.…”
Section: Introductionmentioning
confidence: 99%